Pengaruh Pemasaran Digital dan Getuk Tular Terhadap Keputusan Pembelian - Margaretha Sartien Kabanga; Yefta Sanam (Univiversitas Dr. Djar Wattiheluw, 2023)
This study aims to investigate the influence of digital marketing and word of mouth on the purchase decision at Papa Ganteng Kupang Coffee Shop. The research adopts an associative approach and collects data through a questionnaire distributed to the customers of Papa Ganteng Kupang Coffee Shop. The required sample for this study is 100 respondents, selected using purposive sampling technique. Data analysis includes instrument quality test, classical assumption test, and multiple linear regression analysis using SPSS software. The research findings reveal that digital marketing and word of mouth have a significant positive impact, both simultaneously and partially, on the purchase decision at Papa Ganteng Kupang Coffee Shop. Furthermore, it is evident that digital marketing exerts a more dominant influence compared to word of mouth, as it is more effective in shaping the purchase decision at Papa Ganteng Kupang Coffee Shop.